SOLVING TWO-DIMENSIONAL TIME-SPACE FRACTIONAL DIFFUSION PROBLEM BY USING LEAST-SQUARES-PETROV-GALERKIN METHOD - Jumaa, Sara Qasim; Al- Humedi, Hameeda Oda (International Journal Multidisciplinary (IJMI), 2026)
Objective: Nanotechnology (nano: One billionth) is a novel arena with promising applications in the field of medicine, especially pharmaceuticals for safe and targeted drug delivery. The skin is a phenomenal tool for investigation of nanocarriers for drug delivery for topical and dermatological application. Method: The physicochemical characteristics of the nanoparticles, such as rigidity, hydrophobicity, size and charge are crucial to the skin permeation mechanism. Even though different ways have been found to make therapeutics penetrate and permeate the skin better, they are often harsh and could cause permanent damage to the stratum corneum. Results: Nanosized carrier systems offer a novel methodology for contemporary technologies, causing negligible disruption to the skin's natural barrier function. Novelty: This Review discusses the use of Nano carriers to deliver drug molecules, genetic material, and vaccines into the skin, emphasizing nanotoxicology research and recent clinical advancement for market translation.